VALUATION OF BODY WEIGHT ON THE BACKPACK SCHOOL IN A PRIVATE SCHOOL AND A PUBLIC SCHOOL ZONE NORTH PORTO ALEGRE (Fiep Bulletin - online, 2014)
The backpack is the most common method used by students to carry all your school supplies. This method can promote poor posture, especially if carried above 10% of body weight. This study aimed to analyze the body weight in relation to school backpack at a private school and a public school, to know whether to use their backpacks within the maximum weight. Characterized by an observational method descriptive analytical cross-concerned with identifying backpack weight of primary school students. Those responsible for the research participants were in accordance with the Resolution 196/96. For data collection, we used the "Instrument for Knowledge Perception of Students on Environment Posture Adopted School - POSPER. Sample consisted of 398 students, students from 1st to 5th grade of elementary school. The results showed high level of ignorance about the existence of the Law of Backpacking, recommending its weight. We found that more than half of the students carry the school backpack with adequate weight, ie, within 10% of body mass allowed, a value recommended by WHO (2004). On the transport of school supplies, it was observed that the students of 1st year public and 2nd year private use backpack rollaway and students of the 1st, 3rd, 4th and 5th year of private school and the 2nd, 3rd, 4th and 5th year public school carrying their stuff in the back with straps over both shoulders. From the results, it is concluded that public school students and the 1st and 4th year of private school are normal, and the pupils of the 2nd, 3rd and 5th year of private school are transporting material over 10% of the weight body allowed by law.